Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS dengan Menggunakan Metode Role Playing di Sekolah Dasar - Mayastuti, Elvita; Nasrul, Nasrul; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to describe the improvement of student learning outcomes in learning social science knowledge (IPS) using role playing method in the fifth grade in SDN 52/III Koto Dian, Kerinci regency. This study is a classroom action research (PTK) which is uses qualitative and quantitative approach which includes planning, implementation, observation and reflection. The subjects of this study were teachers and students of the fifth grade of 22 people. The observation results of RPP cycle I 85, 6%, cycle II 96, 6%. The teacher activity cycle I 81.3%, cycle II 96, 6%. The student activity cycle I 79, 7%, cycle II 93,8%. Average learning outcomes of student cycle one (I) is 71, 4, and student cycle two (II) is 82, 5. Thus, this study can be concluded that learning social sciendce knowledge (IPS) role playing method can improve student learning outcomes in the fifth grade in SDN 52/III Koto Dian, Kerinci regency. Keywords: learning social science knowledge (IPS), role playing method